PENERAPAN MODEL JIGSAW BERMEDIA MAGIC CIRCLE DALAM MENINGKATKAN HASIL BELAJAR - Maulida, Dea; Hanifah, Nurdinah; Djuanda, Dadan (Jurnal Pena Ilmiah, 2017)
After the observation on 5th grader SDN Darangdan Kecamatan Sumedang Selatan Kabupaten Sumedang, researchers found a problem in student learning outcomes in subjects Social Science material Diversity Tribe Nations and Culture in Indonesia. The low learning outcomes of students are influenced by less optimal performance of teachers and student activities. Therefore it is necessary to solve the problem through the application of model jigsaw by magic circle. This research is a classroom action research (PTK). Target achievement of learning outcomes is 93.33% of the total number of students as many as 30 people with KKM 75. After the implementation of this study the percentage of student learning outcomes exceeded the set target that is, 96.67%. So it can be concluded that the model jigsaw by magic circle can improve student learning outcomes on the material Ethnic and Cultural Diversity in Indonesia.